2023
DOI: 10.1186/s13148-023-01597-4
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic age acceleration in surviving versus deceased COVID-19 patients with acute respiratory distress syndrome following hospitalization

Yosra Bejaoui,
Fathima Humaira Amanullah,
Mohamad Saad
et al.

Abstract: Background Aging has been reported as a major risk factor for severe symptoms and higher mortality rates in COVID-19 patients. Molecular hallmarks such as epigenetic alterations and telomere attenuation reflect the biological process of aging. Epigenetic clocks have been shown to be valuable tools for measuring biological age in various tissues and samples. As such, these epigenetic clocks can determine accelerated biological aging and time-to-mortality across various tissues. Previous reports … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…A similar study by our group, using the same epigenetic clocks and surrogate telomere length estimator, observed a significant EAA measured via the Hannum, PhenoAge, and GrimAge clocks in COVID-19 patients with acute respiratory distress syndrome (ARDS). Our study also observed EAA across several phases of the disease ( 49 ). Additionally, comparing DNAmAge in COVID-19 patients who died to those who recovered at both baseline and final follow-up revealed EAA only in the GrimAge clock.…”
Section: Covid-19 and Biological Aging (Ie Epigenetic Age)supporting
confidence: 71%
See 3 more Smart Citations
“…A similar study by our group, using the same epigenetic clocks and surrogate telomere length estimator, observed a significant EAA measured via the Hannum, PhenoAge, and GrimAge clocks in COVID-19 patients with acute respiratory distress syndrome (ARDS). Our study also observed EAA across several phases of the disease ( 49 ). Additionally, comparing DNAmAge in COVID-19 patients who died to those who recovered at both baseline and final follow-up revealed EAA only in the GrimAge clock.…”
Section: Covid-19 and Biological Aging (Ie Epigenetic Age)supporting
confidence: 71%
“…DNAmTL measurements revealed telomere attrition acceleration in deceased COVID-19 patients between inclusion and end of follow-up and a significant change in dynamic telomere attrition acceleration when comparing patients who recovered versus those who died ( 49 ). It was in line with another study where they showed that individuals with severe COVID-19 displayed significant DNAmTL attrition acceleration compared to individuals with non-severe COVID-19 ( 48 ).…”
Section: Covid-19 and Telomere Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the Horvath pan-tissue clock [44] accurately estimates DNA methylation age across the lifespan in most human tissues. Epigenetic age acceleration (EAA) as estimated by the Horvath clock has been robustly associated with both early life exposures and later life morbidity and mortality [45], including respiratory illness outcomes [46]. EAA has also been consistently associated with, and even hailed as an emerging biomarker of asthma and atopic diseases in children [47,48] and may provide insight into the biological embedding of early life chemical exposures on immune system development.…”
Section: Introductionmentioning
confidence: 99%